PENGABDIAN MASYARAKAT EDUKASI DAN SIMULASI PERTOLONGAN PERTAMA KEJANG OTOT DENGAN METODE EDUKASI SUPORTIF TERSTRUKTUR PADA SISWA DI SMK BHAKTI MULIA (STIKES dan AKZI Karya Husada Kediri, 2023)
ABSTRACT Health problems that occur in schools besides illness are injuries. The phenomenon of injury to high school or vocational high school students is synonymous with sports, one of which is muscle cramps, this is supported by the habits of students when sports do not warm up. Lack of information about PMR members about first aid properly. The purpose of this community service is to know first aid for muscle spasms with a structured supportive education method for students at Bhakti Mulia Vocational School. The population is 30 students, a sample of 24 students consists of 6 student PMR cadres, 30 student members. PMR cadres of selected students from PMR Wira who will be empowered. Cadres are expected to be able to continue the Structured Supportive Education method of first aid for muscle spasms to the entire PMR population. The community service instrument uses a questionnaire sheet. The results of PMR members before the intervention were 10 people 48.38% in the good category, after the intervention as many as 15 54.83% good ability. This means that PMR members experience an increase in the first aid ability score for muscle spasms. The results of the analysis using the Wilcoxon test obtained sig ρ value = 0.000 with sig α = 0.05 so that the ρ value ≤ α. which means there is influence before and after the intervention of PMR members. Structured Supportive Education Method Education is an effort in a persuasive way, providing information, support, providing awareness to individuals through health education / counseling with the aim of making individual behavior conducive to health, namely having a positive effect on maintaining and improving health Keywords: Structured Supportive Education, Muscle Spasms, PMR